A new species of armored scale (Hemiptera: Coccoidea: Diaspididae) found on avocado fruit from Mexico and a key to the species of armored scales found on avocado worldwide - Evans, Gregory A.; Watson, Gillian W.; Miller, Douglass R. (Zootaxa, 2009)
A new species of armored scale, Abgrallaspis aguacatae Evans, Watson, and Miller spec. nov. is described and illustrated from specimens collected on avocado fruit from Mexico. This species has caused considerable concern as a quarantine issue in the United States. A key to the armored scale species known to feed on avocado worldwide is provided.